Allocation pattern, ion partitioning, and chlorophyll a fluorescence in Arundo donax L. in responses to salinity stress. (4th July 2017) - Pompeiano, A.; Landi, M.; Meloni, G.; Vita, F.; Guglielminetti, L.; Guidi, L.
Abstract: Biometric and physiological analyses of salt stress responses were performed in two time-course experiments on giant reed ( Arundo donax L). Experiment I evaluated biomass production in plants exposed to 128, 256, 512 mM NaCl for 84 days. For Experiment II, plants grown under 256 mM NaCl were further assessed for chlorophyll a fluorescence, ionic partitioning, and proline content at 14 and 49 days after treatment (DAT). Biomass allocation was affected with all the concentrations of NaCl used from 28 DAT onward. Proline biosynthesis in leaves was more stimulated than that in roots after salt stress. Photosynthetic efficiency of photosystem II (PSII) was not affected by salt stress up to 42 DAT, while 49 DAT plants exhibited a significant reduction of both potential (ΦPSII ) and maximal ( F v / F m ) PSII quantum yield. A. donax resulted a moderately sensitive species in response to 256 and 512 mM NaCl, concentrations that are however higher than that commonly found in most marginal lands (such as 128 mM or lower), where the biomass yield is appreciable, especially in short-term cultivation (56 DAT here). Altogether, this study indicates that A. donax can be considered as a promising and valuable energy crop for exploiting the Mediterranean marginal land.